Prinsip Free And Prior Informed Consent Terhadap Perlindungan Masyarakat Adat Atas Tanah Dalam Perspektif Hukum Hak Asasi Manusia Internasional - Ikbal, Ikbal (Lampung University)
The true policy in protection of land indigenuos peoples in Indonesian can be done by implemented the âfree and prior informed consentâ in national and local regulation, as international human right law placing these principle as fundamental principle which internalized in all articles.